LACTOSE AND REDUCTION SUGAR CONCENTRATIONS, PH AND THE SOURNESS OF DATE FLAVORED YOGURT DRINK AS PROBIOTIC BEVERAGE - Ade Irma Hartati (Jurnal Aplikasi Teknologi Pangan, 2012)
Yogurt drink contains of Lactic Acid Bacteria which have lot of functions for health. The growth of Lactic Acid Bacteria depends on heat treatment, how long fermentation takes place, and kinds of sugar in the milk. Adding some sugar to Yogurt drink can optimize the growth of Lactic Acid Bacteria. Date palm was used to add the sugar contain of yogurt drink with different percentage range from 0% (T0), 2% (T1), 4% (T2) and 6% (T3) with 5 times replicated.  To aim the information of the sugar utilities in fermenting milk, so in this study used four parameters, there were lactose concentration, total reduction sugar, pH and level of sourness. Completely Randomized Design was used, data result were analyzed with ANOVA, then were continued with Duncan Multiple Range Test. Finally result showed that adding date palm during fermentation decreasec the lactose concentration from T1 to T3 then increased in T4 with range from 3.19%-3.32%, Reduction Sugar increased persistently from T0 to T3 range from 2.15%-2.99%, and pH value decreased range from 3.83-3.76. However, adding date palm into yogurt drink had no effect in sourness. This study informs that the natural sugar of date palm was used by Lactic Acid Bacteria during fermentation process, so that it affected Lactose and reduced Sugar concentration and pH value.